A low-residual-alkali sodium electric layered-oxide positive electrode material, a preparation method thereof and a secondary battery
Patent Information
- Application Number
- CN202611003987.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-07
- Publication Date
- 2026-09-29
AI Technical Summary
较高的NaOH与Na2CO3残留会引发一系列负面效应,包括恶化材料的电极加工性能、加速电解液分解、增加界面阻抗、导致电芯膨胀、降低循环稳定性,严重时甚至可能引发安全隐患
1.显著降低材料表面残碱,适配高钠体系,无需额外包覆工序。
Smart Images

Figure CN122833694A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery materials technology, and more specifically, to a low-alkali-residue sodium-ion layered oxide cathode material, its preparation method, and a secondary battery. Background Technology
[0002] In sodium-ion battery cathode material systems, O3-type layered oxide single crystal materials have become one of the mainstream technologies due to their relatively simple synthesis process and high energy density, and have already achieved small-scale industrial applications. Currently, O3-type layered oxide single crystal materials (such as NaNi) 1 / 3 Fe 1 / 3 Mn 1 / 3 The synthesis of O2 mainly adopts a single-stage or two-stage sintering process.
[0003] While the aforementioned methods can achieve the synthesis of the target material, their control over residual alkali content remains significantly insufficient, especially in high-sodium stoichiometry systems (Na content greater than 0.9%), where the material often exhibits a high residual alkali content. Although subsequent methods such as surface coating and secondary sintering can reduce residual alkali to some extent, the effect is limited. High levels of NaOH and Na2CO3 residues can trigger a series of negative effects, including deteriorating electrode processing performance, accelerating electrolyte decomposition, increasing interfacial impedance, causing cell expansion, reducing cycle stability, and in severe cases, even posing safety hazards. Summary of the Invention
[0004] This application aims to overcome the shortcomings of the prior art and provide a low-residue sodium-ion battery layered oxide cathode material and its preparation method, as well as a secondary battery containing the cathode material.
[0005] To solve the above-mentioned technical problems, this application adopts the following technical solution.
[0006] This application provides a method for preparing a low-alkali-residue sodium-ion battery layered oxide cathode material, comprising the following steps: sintering a mixture of transition metal oxide or hydroxide precursor and sodium salt under gradient heating without cooling, followed by gradient cooling annealing and segmented heat preservation to obtain the low-alkali-residue sodium-ion battery layered oxide cathode material.
[0007] This application also provides a low-residue sodium-ion battery layered oxide cathode material obtained by the above preparation method.
[0008] This application also provides a secondary battery comprising the aforementioned low-alkali-residue sodium-ion battery layered oxide cathode material.
[0009] This application has the following beneficial effects: 1. Significantly reduces residual alkali on the material surface, suitable for high-sodium systems, and requires no additional coating process.
[0010] 2. The single-crystal structure is complete, and the grain size is uniform and controllable, avoiding structural defects caused by rapid cooling.
[0011] 3. Improve electrode processing performance, reduce moisture absorption and clumping, and enhance coating uniformity and production yield.
[0012] 4. Suppress electrolyte side reactions, reduce interfacial impedance and gas generation risk, and improve battery cycle stability and safety.
[0013] 5. The process is compatible with existing sintering equipment, the steps are simple and controllable, and it is easy to carry out industrial mass production. Attached Figure Description
[0014] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0015] Figure 1 The image shows the XRD pattern of the low-alkali-residue sodium-ion layered oxide cathode material obtained in Example 1. Figure 2 SEM image of the low-alkali-residue sodium-ion layered oxide cathode material obtained in Example 1; Figure 3 SEM image of the low-alkali-residue sodium-ion layered oxide cathode material obtained in Comparative Example 1; Figure 4 This is a comparison of the coin cell cycle performance at room temperature of the low-alkali-residue sodium-ion layered oxide cathode materials obtained in Example 1 and Comparative Example 1. Detailed Implementation
[0016] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0017] The following is a detailed description of a low-alkali-residue sodium-ion layered oxide cathode material, its preparation method, and a secondary battery provided in the embodiments of this application.
[0018] In one aspect, this application provides a method for preparing a low-alkali-residue sodium-ion layered oxide cathode material. Through a multi-stage sintering process of "low-temperature pre-sintering - high-temperature nucleation - gradient cooling annealing," the method aims to significantly reduce the surface residual alkali of the single-crystal material while ensuring the integrity and controllable size of the crystal.
[0019] The specific steps are as follows: Mixing: Mix Na2CO3 with a precursor (such as Ni) 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2) Mix evenly according to the stoichiometric ratio.
[0020] Low-temperature preheating (first stage): Temperature range: 700~900℃.
[0021] Insulation time: 2 to 6 hours.
[0022] During the low-temperature pre-calcination stage, the sodium salt begins to melt and react with the precursor, initially forming a layered oxide framework and releasing gas to provide nuclei for subsequent single crystal growth.
[0023] High-temperature sintering (second section): Temperature range: 1000~1100℃.
[0024] Insulation time: 6-10 hours (the specific time is adjusted according to the required single crystal particle size; if larger particles are required, the time should be extended appropriately).
[0025] The high-temperature sintering stage promotes the full growth and fusion of primary grains, forming micron-sized single-crystal primary particles. During the high-temperature sintering stage, the grains grow fully, but some sodium is lost through volatilization. Sodium has high solubility in the crystal lattice at high temperatures. If the temperature is directly and rapidly reduced, supersaturated sodium will precipitate on the surface to form free alkali. Therefore, gradient cooling annealing is required to control the distribution of sodium.
[0026] Gradient cooling annealing (segment 3 to N): After high-temperature sintering, instead of allowing the temperature to cool naturally, a gradient cooling annealing process is performed, with each stage of cooling ranging from 50 to 150°C. This gradient can be in two, three, or four stages, with each stage requiring a holding time of at least one hour.
[0027] Specific example (three-stage gradient cooling): First cooling stage: cooling from 1020℃ to 920℃, and holding at 920℃ for 2 hours.
[0028] The second cooling stage: the temperature is reduced from 920℃ to 820℃, and then kept at 820℃ for 2 hours.
[0029] The third cooling stage: cooling from 820℃ to room temperature (natural cooling or controlled cooling can be used).
[0030] After high-temperature sintering, instead of rapid cooling, the temperature is gradually reduced in a higher temperature range and then held in sections. Sodium ions still have strong diffusion capabilities within this temperature range. Sufficient holding time allows excess sodium and unstable sodium on the surface to diffuse back into the bulk lattice and re-intercalate, repairing surface sodium defects and thus reducing the residual alkali content on the surface.
[0031] Secondly, this application also provides a low-alkali-residue sodium-ion layered oxide cathode material prepared by the above-described preparation method. The low-alkali-residue sodium-ion layered oxide cathode material is an O3 type single crystal with space group R-3m, a size of 3-10 micrometers, a surface residual alkali content of NaOH < 500 ppm, Na2CO3 < 8000 ppm, and a 0.1C reversible specific capacity > 130 mAh / g.
[0032] Thirdly, this application also provides a secondary battery, including the aforementioned low-alkali-residue sodium-ion layered oxide cathode material.
[0033] The present application will be further described below with reference to embodiments.
[0034] Example 1 A method for preparing a low-alkali-residue sodium-ion layered oxide cathode material, the specific steps of which are as follows: Step 1, Mixing: Mix Na2CO3 with Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 is mixed evenly according to the stoichiometric ratio.
[0035] Step 2, Low-temperature preheating (first stage): Insulation temperature: 800℃.
[0036] Insulation time: 4 hours.
[0037] Step 3, High-temperature sintering (second stage): Temperature: 1020℃.
[0038] Insulation time: 8 hours (the specific time is adjusted according to the required single crystal particle size; if larger particles are required, the time should be extended appropriately).
[0039] Step 4, Gradient cooling annealing (third to fifth stages): The third cooling stage: cooling from 1020℃ to 920℃, and then maintaining the temperature at 920℃ for 2 hours.
[0040] The fourth cooling stage: the temperature is reduced from 920℃ to 820℃, and then maintained at 820℃ for 2 hours.
[0041] Fifth cooling stage: Cool down from 820℃ to room temperature, allowing it to cool naturally.
[0042] After cooling, the cathode material was collected and subjected to physicochemical and half-cell electrochemical performance tests. Then, test data were collected, including NaOH and Na2CO3 content, 0.1C reversible specific capacity, first-efficiency, 50 cycles at room temperature (25°C), and 50 cycles at high temperature (45°C).
[0043] Example 2: Extending the gradient cooling and heat preservation time Steps 1, 2, and 3 are exactly the same as in Example 1.
[0044] Step 4, gradient cooling annealing: The third cooling stage: cooling from 1020℃ to 920℃, and then maintaining the temperature at 920℃ for 4 hours.
[0045] The fourth cooling stage: the temperature is reduced from 920℃ to 820℃, and then maintained at 820℃ for 4 hours.
[0046] Fifth cooling stage: Cooling down from 820℃ to room temperature.
[0047] Example 3: Changing the sintering temperature in the first stage Step 1 is the same as in Example 1.
[0048] Step 2, Low-temperature preheating (first stage): Insulation temperature: 750℃.
[0049] Insulation time: 4 hours.
[0050] Steps 3 and 4 are exactly the same as in Example 1 (1020℃ / 8h, 920℃ / 2h, 820℃ / 2h).
[0051] Example 4: Changing the sintering temperature in the second stage Steps 1 and 2 are the same as in Example 1.
[0052] Step 3, High-temperature sintering (second stage): Temperature: 1080℃.
[0053] Insulation time: 8 hours.
[0054] Step 4 is exactly the same as in Example 1 (gradient cooling 920℃ / 2h, 820℃ / 2h).
[0055] Example 5: Changing the second-stage heat preservation time Steps 1 and 2 are the same as in Example 1.
[0056] Step 3, High-temperature sintering (second stage): Temperature: 1020℃.
[0057] Insulation time: 6 hours.
[0058] Step 4 is exactly the same as in Example 1.
[0059] Example 6, One-stage gradient cooling Steps 1, 2, and 3 are exactly the same as in Example 1.
[0060] Step 4, gradient cooling annealing: Cooling phase: The temperature is reduced from 1020℃ to 920℃ and held at 920℃ for 2 hours.
[0061] It was then allowed to cool naturally from 920°C to room temperature.
[0062] Example 7, Four-stage gradient cooling Steps 1, 2, and 3 are exactly the same as in Example 1.
[0063] Step 4, gradient cooling annealing: The third cooling stage: cooling from 1020℃ to 920℃, and then maintaining the temperature at 920℃ for 2 hours.
[0064] The fourth cooling stage: the temperature is reduced from 920℃ to 820℃, and then maintained at 820℃ for 2 hours.
[0065] The fifth cooling stage: the temperature is reduced from 820℃ to 720℃, and then maintained at 720℃ for 2 hours.
[0066] The sixth cooling stage: cooling from 720℃ to room temperature.
[0067] Example 8, changing the type of sodium salt Step 1, Mixing: Mix NaNO3 with Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 is mixed evenly in a molar ratio of 0.95:1.
[0068] Steps 2, 3, and 4 are exactly the same as in Example 1 (800℃ / 4h, 1020℃ / 8h, gradient cooling 920℃ / 2h, 820℃ / 2h).
[0069] Comparative Example 1, Gradient-free cooling Steps 1, 2, and 3 are exactly the same as in Example 1.
[0070] Step 4, Cooling method: Directly cool from 1020℃ to room temperature naturally, without any heat preservation annealing.
[0071] Comparative Example 2: Gradient cooling and heat preservation time less than 1 hour Steps 1, 2, and 3 are exactly the same as in Example 1.
[0072] Step 4, gradient cooling annealing: The third cooling stage: cooling from 1020℃ to 920℃, and holding at 920℃ for 0.5 hours.
[0073] The fourth cooling stage: cooling from 920℃ to 820℃, and holding at 820℃ for 0.5 hours.
[0074] Fifth cooling stage: Cooling down from 820℃ to room temperature.
[0075] Comparative Example 3: No gradient heating, only one-stage high-temperature sintering. Step 1 is the same as in Example 1.
[0076] Step 2, high-temperature sintering: The mixture is directly kept at 1020℃ for 12 hours.
[0077] Step 3, gradient cooling annealing: exactly the same as step 4 in Example 1 (1020℃→920℃ / 2h→820℃ / 2h→room temperature).
[0078] Comparative Example 4, sodium content is less than 0.9%. Step 1, Mixing: Mix Na2CO3 with Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 is mixed evenly in a molar ratio of 0.85:1.
[0079] Steps 2, 3, and 4 are exactly the same as in Example 1 (800℃ / 4h, 1020℃ / 8h, gradient cooling 920℃ / 2h, 820℃ / 2h).
[0080] Comparative Example 5, sodium content higher than 1.0. Step 1, Mixing: Mix Na2CO3 with Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 is mixed evenly in a molar ratio of 1.05:1.
[0081] Steps 2, 3, and 4 are exactly the same as in Example 1 (800℃ / 4h, 1020℃ / 8h, gradient cooling 920℃ / 2h, 820℃ / 2h).
[0082] Comparative Example 6, the first stage sintering temperature is below 700℃ Step 1 is the same as in Example 1.
[0083] Step 2, Low-temperature preheating (first stage): Insulation temperature: 650℃.
[0084] Insulation time: 4 hours.
[0085] Steps 3 and 4 are exactly the same as in Example 1 (1020℃ / 8h, gradient cooling 920℃ / 2h, 820℃ / 2h).
[0086] Comparative Example 7, the second-stage sintering temperature is higher than 1100℃. Steps 1 and 2 are the same as in Example 1.
[0087] Step 3, High-temperature sintering (second stage): Temperature: 1120℃.
[0088] Insulation time: 8 hours.
[0089] Step 4 is exactly the same as in Example 1 (gradient cooling 920℃ / 2h, 820℃ / 2h).
[0090] Comparative Example 8: The second-stage heat preservation time was too short. Steps 1 and 2 are the same as in Example 1.
[0091] Step 3, High-temperature sintering (second stage): Temperature: 1020℃.
[0092] Insulation time: 2 hours.
[0093] Step 4 is exactly the same as in Example 1.
[0094] Comparative Example 9: The temperature drop during the cooling phase was too high. Steps 1, 2, and 3 are exactly the same as in Example 1.
[0095] Step 4, gradient cooling annealing: The third cooling stage: the temperature is reduced from 1020℃ to 770℃, and then maintained at 770℃ for 2 hours.
[0096] The fourth cooling stage: the temperature is reduced from 770℃ to 520℃, and then maintained at 520℃ for 2 hours.
[0097] Fifth cooling stage: Cooling down from 520℃ to room temperature.
[0098] The sintering temperatures of the materials in the above embodiments and comparative examples are summarized in Table 1.
[0099] Performance testing The cathode materials obtained in Examples 1-8 and Comparative Examples 1-9 were first prepared into coin cells, and then the performance of the coin cells was tested. The preparation method of the coin cells is as follows: Low-alkali sodium-ion layered oxide cathode material, polyvinylidene fluoride (PVDF), and acetylene black were mixed and stirred evenly in a mass ratio of 90:5:5. Then, a certain amount of N-methylpyrrolidone (NMP) was added and stirred continuously until the mixture became a uniform slurry. This slurry was then uniformly coated onto aluminum foil.
[0100] The coated aluminum foil was placed in a vacuum oven and dried at 110°C, and then pressed by a roller press (compacted density: 3.2 g / cm³). 3 (This process is repeated to make the surface smooth and even, and then dried in a vacuum oven at 120°C for 12 hours.)
[0101] The dried aluminum foil sheets were cut, weighed, and assembled into batteries in a glove box. The electrolyte used was a 1 mol / L dimethyl carbonate (DMC) / ethylene carbonate (EC) solvent (volume ratio 1:1). The electrode sheet and sodium sheet were used as the positive and negative electrodes, respectively, and assembled into a button-type half-cell using the glove box.
[0102] The test conditions were as follows: voltage window of 2.0~4.0V, stand for 5 hours before test, complete activation rate test at 0.1C, 0.2C, 0.5C and 1C, and then cycle at 1C for 50 times. The test results were recorded and are shown in Table 2.
[0103] Table 1. Synthesis parameters of materials used in examples / comparative examples
[0104] Table 2 Comparison of Physicochemical / Choose-Cellular Properties of Materials in Examples / Comparative Examples
[0105] Combining Tables 1 and 2 above and Figures 1-4It can be seen that the obtained material exhibits typical O3-type layered oxide diffraction peaks, corresponding to space group R-3m, with no obvious impurity phase peaks, indicating that the product is a pure-phase O3-type layered structure with a particle size D50 of approximately 6 micrometers. As the pre-sintering temperature decreases, the sintering temperature increases, the number of annealing stages decreases, and the high-temperature holding time shortens, the residual alkali content of the material gradually increases. Examples using a pre-sintering temperature not lower than 750℃, a sintering temperature not higher than 1080℃, a high-temperature holding time not lower than 6 hours, and employing two or more gradient annealing stages can stably achieve low residual alkali levels of NaOH < 500ppm and Na2CO3 < 8000ppm, with a reversible specific capacity of > 130mAh / g at 0.1C. In Comparative Example 1, the lack of gradient cooling and direct cooling resulted in insufficient time for surface residual alkali to diffuse or stabilize, leading to significant residue, hindering ion transport, and deteriorating capacity and cycling performance. As can be seen from the SEM images of Example 1 and Comparative Example 1, the multi-segment sintering results in more uniform grain size, smoother surface, and a significant reduction in fine powder particles, which is beneficial for improving electrochemical performance (see comparison of coin cycle performance). Figure 4In Comparative Example 2, when the holding time was less than 1 hour, the gradient annealing effect on reducing residual alkali was insufficient, failing to achieve the low residual alkali index of NaOH < 500 ppm and Na2CO3 < 8000 ppm. Electrochemical performance differences were not significant under short cycles, but the interface stability and gas generation risk under long cycles and high temperatures were inferior to the fully annealed sample. In Comparative Example 3, there was no gradient heating and a lack of low-temperature pre-calcination, resulting in uneven precursor decomposition and initial phase formation, easily generating impurity phases and residual alkali, with numerous structural defects, and poor first-time performance and cycling performance. In Comparative Example 4, the sodium content was < 0.9%, resulting in a sodium-deficient phase and low reversible sodium intercalation / deintercalation capacity. In Comparative Example 5, the sodium content was > 1.0%. When the sodium content was too high, the excess sodium could not be fully intercalated into the crystal lattice and remained free on the material surface, leading to excessive residual alkali and poor electrochemical performance. In Comparative Example 6, when the pre-sintering temperature was below 700℃, the homogeneity of the precursor phase decreased, leading to an increase in the residual alkali content of the final material. Subsequent high-temperature sintering could compensate for most of the structural defects, so the short-cycle electrochemical performance did not deteriorate significantly. However, the grain size distribution became wider, which was detrimental to batch stability in industrial production. In Comparative Example 7, the second stage was above 1100℃. When the sintering temperature was above 1100℃, sodium volatilization intensified, the bulk sodium content decreased, and the reversible capacity slightly decreased. At the same time, abnormal grain growth was prone to occur, and the cycle stability deteriorated. Because sodium salt decomposes more completely at high temperatures, the residual sodium carbonate content actually decreased. Although a lower residual sodium carbonate could be obtained in this temperature range, the intensified sodium volatilization led to a decrease in reversible capacity and abnormal grain growth, resulting in a decrease in cycle stability. Overall, the electrochemical performance and process adaptability were inferior to the 1000-1100℃ range. In Comparative Example 8, the second stage was too short, the high-temperature reaction was insufficient, the crystal growth was incomplete, the residual sodium carbonate was not completely consumed, the residual alkali was high, the structural integrity was poor, and both the capacity and cycle life were low. In Comparative Example 9, the cooling rate during the cooling stage was too large, and the single-stage cooling rate was too large. This would skip the high diffusion temperature range of sodium, significantly weaken the residual alkali reduction effect of gradient annealing, and the residual alkali content would increase significantly. The electrochemical performance difference within short cycles was small, but the high residual alkali would accelerate the interfacial side reactions and cell gas generation under long cycles, resulting in a decrease in long-term reliability.
[0106] In summary, this application provides a low-alkali-residue sodium-ion layered oxide cathode material, its preparation method, and a secondary battery. The low-alkali-residue sodium-ion layered oxide cathode material is prepared through a multi-stage sintering process of "low-temperature pre-firing - high-temperature nucleation - gradient cooling annealing," achieving the following significant technical effects, which are interconnected and synergistically enhanced: (1) Significant reduction in residual alkali content: By rationally designing the pre-calcination temperature and gradient cooling annealing section, Na2CO3 can participate in the reaction more uniformly during the nucleation stage; during the step-cooling annealing, sufficient holding time is provided in the temperature range where sodium ions still have high diffusion activity, allowing excess sodium and unstable sodium on the surface to diffuse back into the bulk lattice and re-intercalate, repairing surface sodium defects. These factors together significantly reduce the residual alkali content on the material surface in the form of NaOH and Na2CO3, which is especially suitable for high sodium systems (0.9 < Na content < 1.0).
[0107] (2) Balancing crystal structure integrity and size controllability: Low-temperature pre-sintering provides uniform crystal nuclei, and high-temperature sintering promotes the full growth and fusion of primary grains to form micron-sized single crystal particles. Gradient cooling annealing reduces residual alkali and reduces problems such as crystal structure distortion and grain cracking caused by natural cooling, ensuring the integrity of the single crystal material structure and uniform grain size, meeting the single crystal particle size requirements of different scenarios (the high-temperature sintering holding time can be adjusted).
[0108] (3) Improved material processing performance: Reduced residual alkali content, reduced moisture absorption and agglomeration of materials during electrode preparation, improved dispersibility and fluidity, enhanced uniformity and density of electrode coating, reduced process difficulty, and improved production efficiency and product qualification rate.
[0109] (4) Significantly optimized battery electrochemical performance: Reducing surface residual alkali can reduce the probability of it reacting with the electrolyte, reduce electrolyte decomposition products, and lower battery interface impedance; at the same time, it reduces the probability of cell bulging, improves the cycle stability, rate performance and safety performance of sodium-ion batteries, and extends service life.
[0110] (5) The process is feasible and the cost is controllable: This process is realized on the basis of existing sintering equipment. No new special equipment is needed. By optimizing the sintering stage and parameters, the residual alkali can be reduced and the crystal performance can be improved. The steps are simple and easy to operate, making it suitable for large-scale industrial production.
[0111] The above are merely preferred embodiments of this application and are not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A method for preparing a low-alkali-residue sodium-ion layered oxide cathode material, characterized in that, Includes the following steps: The low-alkali-residue sodium-ion layered oxide cathode material is prepared by sintering a mixture of transition metal oxide or hydroxide precursors and sodium salts under gradient heating without cooling, followed by gradient cooling annealing and segmented holding.
2. The preparation method according to claim 1, characterized in that, The molar ratio of Na in the sodium salt to the transition metal in the precursor is 0.9 to 1.
0.
3. The preparation method according to claim 1, characterized in that, The gradient heating sintering includes a first-stage sintering and a second-stage sintering.
4. The preparation method according to claim 3, characterized in that, The first stage of sintering is sintered at a temperature of 700–900℃ and held for 2–6 hours. The second stage of sintering is sintered at a temperature of 1000–1100℃ and held for 6–10 hours.
5. The preparation method according to claim 1, characterized in that, The gradient cooling annealing consists of at least one step cooling stage, and the holding time after each cooling stage is ≥1 hour.
6. The preparation method according to claim 5, characterized in that, The temperature drop range for each stage is 50–150°C, and preferably the gradient cooling annealing includes 2–3 stages of gradient cooling.
7. The preparation method according to claim 1, characterized in that, The sodium salt includes at least one of sodium carbonate, sodium nitrate, and sodium hydroxide, and the transition metal element in the precursor includes at least one of Mn, Ni, and Fe, and may also include at least one of Co, Cu, V, and Cr.
8. A low-alkali-residue sodium-ion layered oxide cathode material prepared by the preparation method according to any one of claims 1 to 7.
9. The low-alkali residual sodium-ion layered oxide cathode material according to claim 8, characterized in that, The low-alkali-residue sodium-ion layered oxide cathode material is an O3 type single crystal with space group R-3m and a size of 3-10 micrometers. Preferably, the residual alkali content on the surface of the material is NaOH < 500ppm, Na2CO3 < 8000ppm, and 0.1C reversible specific capacity > 130mAh / g.
10. A secondary battery, characterized in that, It includes the low-residue sodium-ion layered oxide cathode material as described in claim 8 or 9.